2007
DOI: 10.1088/0022-3727/40/13/r01
|View full text |Cite
|
Sign up to set email alerts
|

Photonic and phononic quasicrystals

Abstract: This review focuses on the peculiarities of quasiperiodic order for the properties of photonic and phononic (sonic) heterostructures. The most beneficial feature of quasiperiodicity is that it can combine perfectly ordered structures with purely point-diffractive spectra of arbitrarily high rotational symmetry. Both are prerequisites for the construction of isotropic band gap composites, in particular from materials with low index contrast, which are required for numerous applications. Another interesting prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
165
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(167 citation statements)
references
References 130 publications
(142 reference statements)
0
165
0
2
Order By: Relevance
“…In the high ⌬⑀ regime, the strong scattering leads to gaps based on Bragg reflection from the locally distorted four-or sixfold ordering. These gaps, which correlate with those of more conventional structures, can also be viewed in terms of the Mie resonance condition for single rods [3]. For low ⌬⑀, the long-range interaction permits sampling of the sunflower's unique spiral structure.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In the high ⌬⑀ regime, the strong scattering leads to gaps based on Bragg reflection from the locally distorted four-or sixfold ordering. These gaps, which correlate with those of more conventional structures, can also be viewed in terms of the Mie resonance condition for single rods [3]. For low ⌬⑀, the long-range interaction permits sampling of the sunflower's unique spiral structure.…”
mentioning
confidence: 90%
“…Many of their potential applications require a complete photonic bandgap (PBG), which is more readily achieved in lattices with high rotational symmetry. Aperiodic crystals, or quasi-crystals, may possess arbitrarily high local or statistical symmetry, suggesting wider isotropic gaps in weakly modulated ͑⌬⑀ Ͻ 3͒ structures [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deterministic aperiodic spatial patterns, dubbed photonic quasicrystals [14][15][16][17][18][19][20][21], display stunning optical responses that cannot be found in either periodic or random systems. Among other issues, they include a self-similar energy spectrum [22,23], a pseudo-bandgap of forbidden frequencies [24][25][26], and critically localized states [27,28] whose wave functions are distinguished by power law asymptotes and self-similarity [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…However, the concept of order without periodicity has been studied extensively in science and technology [10]. In fact, some interesting review articles on photonic quasicrystals can be found in the literature [11,12]. It has been demonstrated that photonic quasicrystals can also exhibit photonic band gaps [13][14][15].…”
Section: Introductionmentioning
confidence: 99%